Role of nano-SiO2 on the performance of microporous foamed polystyrene polymer. Issue 1 (1st January 2019) - Guo, Anfu; Li, Hui; Xu, Jie; Li, Jianfeng; Li, Fangyi
Abstract: Microporous foamed polymers are widely used in numerous fields hence, research on these materials has great practical significance. In this work, the effects of nano-SiO2 on the micromorphology of polystyrene (PS) microporous foamed materials were systematically studied by varying nano-SiO2 content and foaming temperature. Relative to PS, the results show that addition of nano-SiO2 significantly affects the foaming of PS materials. The use of nano-SiO2 as a nucleating agent reduces the size and increases the density of the cells in the PS matrix. Moreover, the addition of nano-SiO2 reduced the viscoelasticity and resistance in the foaming process, whereas the expansion ratio improved. A foamed material with minimum standard deviation of the cell diameter was obtained using PS with 3% nano-SiO2 content. The addition of nano-SiO2 led to an increase in the foaming temperature of the foaming material with the maximum expansion ratio as well as the one having the maximum cell diameter. Further, this addition also led to flattening of the expansion ratio curve in the region of the maximum expansion ratio.